Embark on a journey of knowledge! Take the quiz and earn valuable credits.
Take A QuizChallenge yourself and boost your learning! Start the quiz now to earn credits.
Take A QuizUnlock your potential! Begin the quiz, answer questions, and accumulate credits along the way.
Take A QuizCareer Talk Work & Career 2 years ago
Posted on 16 Aug 2022, this text provides information on Work & Career related to Career Talk. Please note that while accuracy is prioritized, the data presented might not be entirely correct or up-to-date. This information is offered for general knowledge and informational purposes only, and should not be considered as a substitute for professional advice.
No matter what stage you're at in your education or career, TuteeHub will help you reach the next level that you're aiming for. Simply,Choose a subject/topic and get started in self-paced practice sessions to improve your knowledge and scores.
Career Talk 1 Answers
Career Talk 1 Answers
Career Talk 2 Answers
Career Talk 2 Answers
What are the most effective strategies for improving organic traffic in 2025?
Ready to take your education and career to the next level? Register today and join our growing community of learners and professionals.
manpreet
Best Answer
2 years ago
Newton's second law of motion is F = MA. Thus, Ft = mv - mu. Now, when F = 0, then v = u. In the absence of force, the object continues to move with same velocity throughout. Now, when F = 0 and u = 0, then v = 0. That is, an object at rest will remain at rest if no force is acting on it. Thus, Newton's first law is derived from second law. Now, let us consider a system of 2 bodies 1 and 2, and consider that there is no external force acting. Now, let F12 be the force acting on 2 by 1 & F21 be the force acting on 1 by 2. The rate of change of momentum of 1 = dp1/dt and rate of change of momentum of 2 = dp2/dt. Thus, according to Newton's second law of motion F12 = dp2/dt and F21 = dp1/dt Adding both the above equations, we get F12 + F21 = dp2/dt + dp1/dt = d(p2+p1)/dt We know that, no force is applied. Thus, momentum change will also be 0 because no change in velocity occurs. Thus, d(p1 + p2)/dt = 0 Therefore, F12 + F21 = 0 That is, F12 = - F21. Thus, Newton's third law is proved with Newton's second law.